Diagnóstico técnico y operativo del sistema de acueducto de Combia administrado por la E.S.P AcuaCombia. (2020)
The Acuacombia’s aqueduct system is made up by three supply systems, El Pital, San Vicente and Monos, which supply drinking water to certain paths in the townships of Combia Alta and Combia Baja. This document compiles the surveys of the structures that make up the aqueduct system and the hydraulic simulation of the distribution network. In the first instance, a survey of the intake and sand remover structures was carried out; This allowed to identify the physical deficiencies of these hydraulic structures. It is necessary to clarify that these structures were built by the federation of coffee growers for the service of specific communities and there are not design memories, service parameters nor criteria used by the designers for each construction. Naturally, it is important to make a correlation between the existing structures and the mandatory by Resolution 0330 of 2017 known as the Technical Regulation for the Drinking Water and Basic Sanitation Sector, RAS 2017; however, the hydraulic evaluation of the intake and sand remover components are not part of the objectives of this investigation. Finally, an update and simulation of the distribution network draw from the information available by the Aqueduct and Sewer Company and the field work of this network were carried out. Thanks to this simulation, it is possible to know with certainty, the areas where the pressure and speeds stipulated by RAS 2017 are not adequate for the type of population it serves. In conclusion, this research will serve as a fundamental input to Acuacombia E.S.P to prioritize actions and interventions in the network that they administer, thinking of a service improvement plan and compliance with current environmental and sanitation legislation.